2018
DOI: 10.1111/acfi.12369
|View full text |Cite
|
Sign up to set email alerts
|

Working with monsters: counting the costs of workplace psychopaths and other toxic employees

Abstract: We explore the role of 'Workplace Monsters' in the global burden of disease, including the $US1.15 trillion annual cost of depressive and anxiety disorders. We propose the productivity drain created by these individuals is a wicked problem, integrating several disciplines to position workplace monsters as significant corporate governance issues for organisations. Our discussion covers Monster prevalence, impacts on fellow workers and estimates of the costs incurred to business. We classify Monsters as 'appreci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…Depressive and anxiety disorders linked to toxic employees have been estimated to cost 1.15 trillion U.S. Dollars annually (Michalak & Ashkanasy, 2018). Previous studies of hospitality workers in the U.K. have suggested that over 56% had been harassed by a member of the public and nearly 27% by a manager (Unite, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Depressive and anxiety disorders linked to toxic employees have been estimated to cost 1.15 trillion U.S. Dollars annually (Michalak & Ashkanasy, 2018). Previous studies of hospitality workers in the U.K. have suggested that over 56% had been harassed by a member of the public and nearly 27% by a manager (Unite, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…9 For example, Asbi et al (2020) examine recovery from the Black Saturday bushfires. Further, Xue et al (2019) consider financial well-being amongst elderly Australians, while Michalak and Ashkanasy (2020) investigate workplace psychopaths and other toxic employees. In terms of grand challenges, Quayle et al (2019) take on the grand challenge of refugee crises, and Groen (2019), the grand challenge of zero growth economies.…”
Section: Introductionmentioning
confidence: 99%
“…Further, Xue et al . (2019) consider financial well‐being amongst elderly Australians, while Michalak and Ashkanasy (2020) investigate workplace psychopaths and other toxic employees. In terms of grand challenges, Quayle et al .…”
Section: Introductionmentioning
confidence: 99%
“…If the toxic workplace problem remains occurring, then it will be a great loss for the organization in terms of productivity and overall performance, not to mention the annual cost of depressive and anxiety disorders for almost $US1.15 trillion (Michalak & Ashkanasy, 2020). In addition, extant literature offers numerous insights and empirical solutions.…”
Section: Introductionmentioning
confidence: 99%